Das moderne Krankenhaus: Ort der "desorganisierten Kriminalität"? - Duttge, Gunnar (Universitätsverlag Göttingen, 2018)
The organizational requirements for an error-free and effective care of patients within a large-scale hospital are high: despite all efforts to improve the process quality and the establishment of risk management systems and reporting systems, there exists the general impression that the processes and communicative challenges are still - in particular with regard to the grown influence of economic factor - prone to error: in case of doubt to the harm of the patients. The topic, which has a medical and organizational sociological, an economic and not least a (criminal-)legal dimension, was the subject of the traditional annual meeting of the Göttingen Institute for Criminal Science in July 2016.